Making salmon : an environmental history of the Northwest fisheries crisis - Taylor, Joseph E., III (Weyerhaeuser environmental book., 1999)
Annotation In the past twenty years the Pacific Northwest has invested billions of dollars to save salmon runs, and the only thing everyone can agree upon is that the effort has largely failed. Scientists, historians, politicians, and journalists have offered many explanations for this "salmon crisis", but few have looked very far into the past or plumbed primary documents necessary to understand the nineteenth-century roots of salmon management. The purpose of Making Salmon is to subvert the way people have thought about salmon management for the last 125 years. It examines the social, cultural, economic, and environmental context of the decline of salmon from the aboriginal fisheries through the advent of industrial fishing and the rise of hatcheries all the way down to the current crisis of the salmon fisheries as they face the threat of collapse today. The essence of the salmon crisis is the struggle to define and solve a complicated environmental and social problem, but resolution has been elusive because participants have little in common except the propensity to deflect blame onto other groups or activities. Commercial and sport fishers, fish culturalists, environmentalists, smelters, irrigators, bargers, and dam agencies have all responded to declining runs in different ways. The preferred political and technological strategies have perpetuated, rather than resolved, problems. The detailed history of those efforts offered in Making Salmon should remind readers of the complexity of the forces driving decline. It should also caution readers against uncritical faith in technology and temper the tendency to moralize and scapegoat. Making Salmon is of critical importance for everyoneinterested in understanding the origins of and finding a solution for the current environmental crisis in the Pacific Northwest